DNA and BSA binding studies of novel tetracationic phthalocyanines - Ozturk, Ramazan; Kalay, Saban; Kalkan, Ayfer; Turkan, Ali; Abasiyanik, Mustafa F.; Bayir, Zehra A.; Gul, Ahmet (World Scientific Publ Co Pte Ltd, 2008)
The novel tetracationic metallophthalocyanines having diethylmethyl amino-ethylsulfanyl groups on the periphery have been synthesized and characterized. The compounds tend to form aggregates in aqueous solutions. The aggregation of ZnPc4+ or CoPc4+, but not that of CuPc4+, was hindered by the addition of surfactants (Triton X-100 and Tween 20). Using absorption and fluorescence spectroscopic techniques, DNA and BSA binding properties of tetracationic ZnPc in the presence of the surfactants were also investigated. Copyright (c) 2008 Society of Porphyrins & Phthalocyanines.
Keywords: cationic phthalocyanines; DNA binding; phthalocyanine-DNA interaction; phthalocyanine-BSA interaction